Pelatihan Tenaga Pendidik dalam Menerapkan Metode Menggambar Bahasa Rupa Gambar Anak - Maya Purnama Sari; Dian Rinjani; Nurul Hidayah (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING OF EDUCATORS IN APPLYING THE DRAWING LANGUAGE METHOD IN THE FORM OF CHILDREN’S PICTURES. Research-based disablement refers to the results of a 2018 study in Bandung City Elementary School which showed 57.14% of low-grade teaching staff used the modeling method of drawing learning so that in the language development scheme the visual images of children did not match their stage of age. Coblong Subdistrict, Bandung City has unique characteristics that live in the middle of the city but still maintain the structure of the urban village. The highest number of public elementary schools in the city of Bandung and does not have special art educators. The purpose of devotion is to provide training to low-grade educators to be able to apply drawing learning methods that are appropriate to the stage of the child's age characterized by visual images of children in accordance with the development of children's visual language development schemes, and can appreciate children's work appropriately. The dedication method uses Action Review with stages, observations, training, assistance, evaluation and follow-up. The results of dedication based on indicators of learning methods that are correlated with the results of children's learning shows that 99% of teaching staff can apply methods that are appropriate to the characteristics of students, age, and appropriate language language schemes. still modeling. Educators are not confused in appreciating children's drawings, because the reference of visual language development schemes and educators can develop creative and interesting material in learning. The follow-up program is a form of appreciation for the needs of educators in the field, from the results of training and mentoring evaluations, educators need book references as a guide in art learning, especially related to drawing methods, children's visual language and ways to appreciate children's drawings.